Promoterless Gene Targeting Approach Combined to CRISPR/Cas9 Efficiently Corrects Hemophilia B Phenotype in Neonatal Mice - Lisjak, Michela; De Caneva, Alessia; Marais, Thibaut; Barbon, Elena; Biferi, Maria Grazia; Porro, Fabiola; Barzel, Adi; Zentilin, Lorena; Kay, Mark A.; Mingozzi, Federico; Muro, Andrés F. (Frontiers in Genome Editing, 2022)
Many inborn errors of metabolism require life-long treatments and, in severe conditions involving the liver, organ transplantation remains the only curative treatment. Non-integrative AAV-mediated gene therapy has shown efficacy in adult patients. However, treatment in pediatric or juvenile settings, or in conditions associated with hepatocyte duplication, may result in rapid loss of episomal viral DNA and therapeutic efficacy. Re-administration of the therapeutic vector later in time may not be possible due to the presence of anti-AAV neutralizing antibodies. We have previously shown the permanent rescue from neonatal lethality in a Crigler-Najjar mouse model by applying an integrative gene-therapy-based approach. Here, we targeted the human coagulation factor IX (hFIX) cDNA into an hemophilia B mouse model. Two AAV8 vectors were used: a promoterless vector with two arms of homology for the albumin locus, and a vector carrying the CRISPR/SaCas9 and the sgRNA. Treatment of neonatal P2 wild-type mice resulted in supraphysiological levels of hFIX being stable 10 months after dosing. A single injection of the AAV vectors into neonatal FIX KO mice also resulted in the stable expression of above-normal levels of hFIX, reaching up to 150% of the human levels. Mice subjected to tail clip analysis showed a clotting capacity comparable to wild-type animals, thus demonstrating the rescue of the disease phenotype. Immunohistological analysis revealed clusters of hFIX-positive hepatocytes. When we tested the approach in adult FIX KO mice, we detected hFIX in plasma by ELISA and in the liver by western blot. However, the hFIX levels were not sufficient to significantly ameliorate the bleeding phenotype upon tail clip assay. Differences in terms of recombination efficacy between mice of different ages Studies using a reporter vector containing the eGFP cDNA showed higher recombination rate in P2 mice compared to adult animals. With this study, we demonstrate an alternative gene targeting strategy exploiting the use of the CRISPR/SaCas9 platform that can be potentially applied in the treatment of pediatric patients suffering from hemophilia, also supporting its application to other liver monogenic diseases. For the treatment of adult patients, further studies for the improvement of the targeting efficiency are still required.